Comments on `An empirical assessment of the residual income valuation model' - Beaver, William H. (Journal of Accounting and Economics, 1999)
The comment reviews major features of the research design of the DMS study. Several opportunities for future research are discussed, including the exploration of the underlying information variables that influence analyst's forecasts.